Can China's trade surplus be reduced with a Renminbi appreciation? - Tjong, Kuo Liang (2009)
The aim of this paper is to show the impact of exchange rate policy on China’s trade surplus using regression analysis. We investigated the impact of exchange rate on China’s trade balance, through its exports and imports. Our results show that the reduction in the trade surplus will be limited as the exchange rate is negatively correlated with both exports and imports, with the latter to a lesser extent. This implies that a Renminbi (RMB) appreciation will reduce exports and have little or no significant effect on imports. Hence, exchange rate policy, alone, will not be able to address the huge trade imbalance that China has with the rest of the world.